Synthesis and Investigation of Algorithm for Estimation of Active Stator Resistance of Asynchronous Motor with Fixed Rotor - D. S. Odnolko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes an algorithm for online identification of active stator resistance. Algorithm synthesis has been developed on the basis of a recursive least squares method. The problem has been solved for induction motor model defined in the stationary stator frame α–β-coordinating system. An analysis of negative factors deteriorating the identifier operation has been made in the paper. The analysis has revealed the following: measured signals are noisy due to quantization and differentiation; dynamic model of an induction motor provides only approximate presentation about actual processes in the electromagnetic system of the machine. The paper presents results of  a system simulation while applying the proposed algorithm that confirm the fact that the estimated value of the active stator resistance tends to a true value with high accuracy. The identification test assumes a fixed rotor and nominal parameters uncertainty, but the flexible structure of the algorithm allows to use it as  for single-phase excitation so for full-phase control of the induction motor with freely rotating motor.